Kepimpinan transformasi : inventori amalan kepimpinan pengetua Sekolah Menengah Kebangsaan daerah Sibu, Sarawak - Ting, Kung Yew (2009)
The purpose of this research is to determine the role of headmaster in implementing ICT at Sekolah Jenis Kebangsaan (Cina) District of South Kulai. Samples of this research were 238 teachers in the District of South Kulai. Questionnaire was used as the instrument for this study. Descriptive statistics were used to identify the role of headmaster in providing the infrastructures ICT in school; the role of headmaster in encouraging teachers of using ICT in school; the role of headmaster to implement ICT usage among teachers in school management aspect; the role of headmaster to implement ICT usage among teachers in teaching and learning aspect in school. In addition, inferential statistics analysis through t-test and one way ANOVA were used to measure the differences in assessment the role of headmaster in implementing ICT at school based on the teachers’ demographic which were gender, age, academic qualifications and teaching experiences. The alpha value for the pilot test conducted was measured at 0.980. The outcome of the research indicates the average of mean score was at moderate level which was at 3.59. This study also showed that there was a significant difference based on the teachers’ gender, age and teaching experiences in the assessment of the role of headmaster in implementing ICT at school. However, there was no significant difference based on the teachers’ academic qualifications in the assessment of the role of headmaster in implementing ICT at school. As a conclusion, researcher forwarded some suggestions to the authorities concerned as guideline to improve the existing weakness in the role of headmaster as ICT catalyst in schools.